(3OhQ GdHUeI ai GdGKHGJ GdLfGFi ai GdbGfhf GdGeGQGJi (B: s (3OQGSI ebGQfI (B/ s - (3QGTO NdaGf SGde GdeSeGQis; (3CMeO YhV HdGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3GfYcS GdJbOe GdYdei ai eLGd Yde GdhQGKI h GcJTGa GdHUeI GdhQGKjI Ydi eNJda eLGdGJ GdMjGI(B: (3MjK Je GdGSJaGOI ai GdeLGd GdWHi h JWhjQ GdRQGYI h GdUfGYI h ZjQgG ef GdeLGdGJ GdCNQi(B: (3h Pdc HGSJZdGd GdJaQO GdJi jJejR Hg cd EfSGf ef MjK Jchjfg h NUGFUg GdLjfjI ai EKHGJ fSH GdhdO dCHjg Ch fai Pdc(B: (3ceG Je GdGSJaGOI efgG ai eLGd GdJMbjbGJ GdLfGFjI h GdHMK Yf eQJcHi GdLQGFe(B. (3h JYO GdHUeI GdhQGKjI (B((3Oi Ef Ejg(B) (3ef CMOK GdJbfjGJ GdYdejI GdMOjbI ai GdYGde ddcTa Yf LQGFe djcf jecf GdJhUd Edi eQJcHjgG HOhf GSJNOGe gPg GdJbfjI GdYdejI (B((3GdHUeI GdhQGKjI(B) (3h jYJHQ gPG GdGcJTGa ef Cbhi GdWQb GdYdejI deYQaI ghjI GdCTNGU ef NdGd NUGFUge GdhQGKjI(B: (3h jDNP cbQjfI bhjI ddMce ai GdbVGjG GdLfGFjI(B: (3HaMU GdBKGQ GdHjhdhLjI GdeJNdaI ai ecGf GdMGOK(B: (3Ch GdbVGjG PGJ GdfRGY GdeOfi(B: (3cbVGjG EKHGJ GdHfhI(B: (3h JMOjO GdfSH(B: (3h bVGjG GdgLQI(B: (3h bVGjG GdeabhOjf(B... (3EdNs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2020s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B163-178s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGKHGJ GdLfGFis; (3GdbGfhf GdGeGQGJis; (3OhQ GdHUeIs; (3TQhW hVhGHW GdHUeI s; (3bhGYO HjGfGJ GdHUeI GdhQGKjI s; (3GdWHjYg GdbGfhfjI ddHUeg s; (3JWHjbGJ GdHUeI GdhQGKjI s; (3eOj eTQhYjI GSJNOGe GdHUeI s; (3GdGSGS GdbGfhfj ddHUeI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs